Global Garveyism - Stephens, Ronald Jemal; Ewing, Adam (Historian) (University Press of Florida, 2019)
This volume--the first edited collection devoted to Garveyism studies in three decades--showcases original essays by scholars working in Africa, the West Indies, the Hispanic Caribbean, North America, and Australia. Garveyism was carried across the globe following the First World War, generating the largest mass movement in the history of the African diaspora.